Analisis Pelaksanaan Pelayanan Kesehatan Berdasarkan Prinsip Good Corporate Governance di Rumah Sakit Umum Daerah (RSUD) Padang Pariaman - Engga Lift Irwanto; Roni Ekha Putera; Ria Ariany (Jurnal Ilmu Sosial dan Ilmu Politik)
This research is due to the many criticisms submitted by the public to hospitals regarding the health care provided to them at unsatisfactory rates, many things complained of the public such as in the case of administrative affairs of very long and cumbersome treatment, the implementation of the provision of unresponsive and responsive care services, the attitude of doctors and nurses unprofessional and unfriendly to the patient, facilities and facilities provided by hospitals are still inadequate, and various other things. The problems that arose then became a matter of consideration for the authorities of the Regional General Hospital Padang Pariaman to promptly carry out improvements and evaluation of service performance in order to regain the trust of the public based on the principle of good corporate governance. The principles of good corporate governance are transparency, accountability, responsibility, independence and justice. Researchers conduct research using descriptive qualitative research methods to describe the implementation of problems in more detail, key research data obtained through the process of interviews with relevant informants and document data as additional data reinforcing research arguments. The results of the research then showed that the Padang Pariaman Regional General Hospital has implemented the overall principle of good corporate governance well in terms of openness of information to the principles of transparency and disqualification of the management of the agency to the principles of accountability. However, the implementation of other principles, especially the principles of responsibility, independence and justice, has not been properly implemented